Hubungan Dukungan Sosial Dengan Self Compassion Pada Mahasiswa Di Masa Pandemi Covid-19 - Harnas, Fanny Anggriani; Gustriani, Tiara; Azra, Muhammad Zein (IAIN Kudus, 2022)
The Relationship between Social Support and Self Compassion for Students During the Covid-19 Pandemic. This study aims to determine the relationship between social support and self-compassion for students in the COVID-19 pandemic. The sample in this study amounted to 270 students (male 19.3% and female 80.7%) Faculty of Psychology UIN Suska Riau with a sampling technique using stratified random sampling. The data collection method in this study used a social support scale and a self-compassion scale. based on the results of the product moment correlation analysis obtained a correlation value of 0.462 with a significance of 0.000. The results showed that the hypothesis was accepted, which means that there is a relationship between social support and self-compassion for students during the COVID-19 pandemic. Further researchers can conduct research on one of the components of self-compassion, namely mindfulness and the type of social support, namely appreciation support. Keywords: Social Support, Self-compassion, Covid-19 Pandemic